Causes of origin and diagnosis of postpunctural false aneurisms of femoral arteries - V. І. Lyakhovskyi; А. V. Sydorenko; R. P. Sakevych; О. М. Bezkorovaynyу; R. М. Rіabushko; Т. А. Voroshуlova (Клінічна хірургія, 2018)
Objective. To estimate the causes of occurrence and quality of diagnosis of false aneurisms (FA) of femoral arteries after endovascular interventions.